2019
DOI: 10.14393/bj-v35n2a20198-41931
|View full text |Cite
|
Sign up to set email alerts
|

Growth and physiology of Annona squamosa L. under different irrigation depths and phosphate fertilization

Abstract: This study aimed to evaluate the growth and physiology of Annona squamosa seedlings under increasing irrigation depths and phosphorus doses. The experiment was conducted in protected environment, evaluating five irrigation depths and four P 2 O 5 doses, arranged in 5 x 4 factorial scheme, in randomized blocks, with four replicates and one plant per plot. Treatments were irrigation depths of 60, 80, 100, 120 and 140% of the real evapotranspiration of the seedlings -ETr and phosphorus doses of 0, 350, 700 and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The optimum growth of pine cone seedlings was obtained with the addition of simple superphosphate in the range of 0.6 to 1.2 kg m -3 . The positive effect of phosphorus addition on the growth of pine cone seedlings are described in other studies (Andrade et al, 2018;Freitas et al, 2013;Moreira et al, 2019) as well as many other species such Annona muricata (Graviola. a Brazilian native fruit) (Soares et al, 2007); Euterpe oleracea (Açaí.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The optimum growth of pine cone seedlings was obtained with the addition of simple superphosphate in the range of 0.6 to 1.2 kg m -3 . The positive effect of phosphorus addition on the growth of pine cone seedlings are described in other studies (Andrade et al, 2018;Freitas et al, 2013;Moreira et al, 2019) as well as many other species such Annona muricata (Graviola. a Brazilian native fruit) (Soares et al, 2007); Euterpe oleracea (Açaí.…”
Section: Resultssupporting
confidence: 53%
“…Studies have shown a beneficial effect of the phosphate fertilization on fruit tree seedlings: açai (Araújo et al, 2018), papaya (Souza et al, 2015), soursop (Soares et al, 2007). To produce pine cone seedlings Araújo et al (1999) recommend 1.5 g dm -3 of simple superphosphate in substrate, while Moreira et al (2019) claim that 350 mg dm -3 provides sufficient dry matter accumulation for pine cone seedlings. Freitas et al (2013) suggest for the initial development of pine cone seedlings, the application of 10.83 mL dm -3 of Cosmofert®.…”
Section: Introductionmentioning
confidence: 99%
“…The literature is abundant regarding relationships between primary and specialized metabolisms under water stress. However, in Annona, studies are generally aimed at evaluating the effect of hydric stress on plant production, especially drought [34,35] or secondary metabolites [18,36]. Thus, there are no reports on how drought and flooding stress affect the primary metabolism and production of alkaloids in Annona emarginata.…”
Section: Introductionmentioning
confidence: 99%
“…However, high salt concentrations in water can compromise the growth, physiology, production, and post-harvest quality of fruits [13]. These disturbances occur mainly due to osmotic effects which reduce water availability for plants [14], toxic effects caused by Cl − and Na + ions [12], and the nutrient imbalance that imposes deficiency of essential nutrients (Ca 2+, Mg 2+ , K + , and NO 3 − ) due to the ion competition caused by the excess of chloride and sodium [15].…”
Section: Introductionmentioning
confidence: 99%